Rozwiąż podane równania i sprawdź.

Odpowiedź:
1. 4 (a - 1) = 6 (1+a) - 4a
4a - 4 = 6 + 6a - 4a
4a - 4 = 6 + 2a
2a = 10
a = 5
Sprawdzenie:
4 * (5-1) = 6 * (1+5) - 4 * 5
4 * 4 = 6 * 6 - 20
16 = 36 - 20
16 = 16
2.
(x-7) - 2(3x+5) = 3-x
x - 7 -6x - 10 = 3 - x
-5x - 17 = 3 - x
-4x = 20
x = -5
Sprawdzenie:
(-5-7) -2 (3*(-5) + 5) = 3 - (-5)
-12 -2 * (-15+5) = 3 + 5
-12 - 2 * (-10) = 8
-12 + 20 = 8
8 = 8
3.
[tex]\frac{1}{3} x - 2 = x + 2\\-4 = \frac{2}{3} x\\-6 = x\\[/tex]
Sprawdzenie:
[tex]\frac{1}{3 } * (-6) - 2 = -6 + 2\\-2 -2 = -4\\-4 = -4[/tex]
4.
[tex]\frac{x-3}{5} = 9-x \\ x - 3 = 45 - 5x\\6x = 48\\x = 8[/tex]
Sprawdzenie:
[tex]\frac{8-3}{5} = 9-8\\\frac{5}{5} =1\\1=1[/tex]
5.
[tex]\frac{2-3x}{4} = \frac{2x-1}{4} +2\\2 - 3x = 2x + 7\\-5x = 5\\x = -1\\[/tex]
Sprawdzenie:
[tex]\frac{2-3*(-1)}{4} = \frac{2*(-1)-1}{4} +2\\\frac{2+3}{4} =-\frac{3}{4} +2\\\frac{5}{4} = \frac{5}{4}[/tex]
6.
[tex]\frac{2x-3}{4} = \frac{3}{4} + x\\2x - 3= 3 +4x\\-2x = 6\\x = -3[/tex]
Sprawdzenie:
[tex]\frac{2*(-3)-3}{4} = \frac{3}{4} + (-3)\\-\frac{9}{4} = -\frac{9}{4}[/tex]